Survival and prognostic factors of childhood acute lymphoblastic leukemia - Emelyana Permatasari; Endang Windiastuti; Hindra lrawan Satari (Paediatrica Indonesiana, 2009)
Background The treatment protocols of childhood acutelymphoblastic leukemia (ALL) have been improved.Some factors such as age, sex, and nutritional status couldinfluence therapy outcome.Objective To study the survival differences among age, sex,and nutritional status groups in childhood ALL.Methods A retrospective Kaplan-Meier survival analysis ofchildhood ALL was performed in Cipto MangunkusumoHospital since January 1st 1998 until December 31st 2003.We excluded patients aged < 1 years, those with L3 subtype,patients with modified chemotherapy protocol, or withincomplete data.Results A total of 252 patients were analyzed. Overallsurvival of 1-2 year old, > 2-< 10 year old, and 10-18 yearold subjects were 57% (95% CI 38 to 76%), 47% (95% CI40 to 54%), and 35% (95% CI 21 to 49%) respectively (P< 0.05). Five-year -event-free survival (EFS) of 1-2 year old,> 2-< 10 year old, and 10-18 year old subjects were 40%,40%, and 16%, respectively (P <0.05). Overall survival ofmale and female subjects were 46% and 53% respectively(P >0.05). Five-year-EFS of male and female subjects were29% and 45% (P >0.05). Overall survival of well-nourished,undernourished, and malnourished patients were 42%50%and 57% respectively (P >0.05). The five-year-EFS of wellnourished, undernourished, and malnourished subjects were33%,38%, and 51%, respectively (P >0.05).Conclusion Childhood ALL aged 1-2 years had the highestsurvival rate while those of 10-18 year old had the lowest. Therewere no survival rate differences between sex and nutritionalstatus groups.